Vegetable production based on waste heat in closed greenhouses considering economic usage and competitiveness of the European Union - Eperjesi, Zoltán (Acta Agraria Debreceniensis, 2013)
The study investigates two professional fields; the questions of vegetable production in greenhouses, the necessary steam supply and heat regulations. The actuality of this investigation is provided by the planning of a combined cycle power plant of 2400 MW in Hungary. According to the plans the steam developing by generating electricity in the power plant can be used to intensify the vegetable production. In my current study I present the experiences and results gathered as member of the research and development team led by Mr. Dr. Sinórós-Szabó.